2020
DOI: 10.1080/02670836.2019.1701272
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a high aluminium addition on the strength and impact behaviour of hot-rolled Nb containing steels

Abstract: An addition of 0.3 wt-% Al has been made to a Nb containing 0.1 wt-% C, 1.4 wt-% Mn steel in an attempt to improve its impact behaviour on hot rolling to 15 mm thick plate; the intention being to replace some of the specifications that currently can only be achieved by the more expensive methods of control rolling or normalising. Previous work had shown that a 0.2 wt-% Al addition to a hot-rolled plain C–Mn steel resulted in the impact transition temperature decreasing by 40°C with no significant change in str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The current authors [8] reported that adding 0.16%Al to HSLA steels enhances toughness considerably without impairing strength. A further study [9] revealed that the addition of 0.018%Nb is beneficial to improve the strength through grain size refinement and precipitation hardening [10,11].…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…The current authors [8] reported that adding 0.16%Al to HSLA steels enhances toughness considerably without impairing strength. A further study [9] revealed that the addition of 0.018%Nb is beneficial to improve the strength through grain size refinement and precipitation hardening [10,11].…”
Section: Introductionmentioning
confidence: 63%
“…In the case of the 0.02%Al bearing steel, N remains in solution rather than precipitating out since no AlN precipitates were observed under the SEM examination. However, increasing the Al content to 0.16% encouraged precipitation of AlN as shown in Figure 3(e,f), as the driving force for precipitation becomes higher and thus Al can remove N from solution [8].…”
Section: The Effect Of Increasing Al Contentmentioning
confidence: 97%
See 3 more Smart Citations